Prevalence of MASLD and Fibrosis Risk in Turkish Adults with Cardiometabolic Risk Factors: A Nationwide Multicenter Study (DAHUDER MASLD Study) - Kirik, Ali; Sumbul, Hilmi Erdem; Koca, Nizameddin; Kilit, Turkan Pasali; Sezer, Sibel Demiral; Binnetoglu, Emine; Dogru, Teoman (Mdpi, 2025)
Introduction: Metabolic dysfunction-associated steatotic liver disease (MASLD) prevalence data in Turkiye is limited. We aimed to determine the nationwide prevalence of MASLD and advanced hepatic fibrosis risk in subjects with cardiometabolic risk factors (CMRF). Despite recent international consensus redefining fatty liver disease terminology, no nationwide MASLD study has been reported in Turkiye. Methods: This cross-sectional study included 14,371 adults with >= 1 CMRF from 44 centers across 31 cities. MASLD was diagnosed using liver ultrasonography plus cardiometabolic criteria. Advanced fibrosis risk was assessed by fibrosis-4 (FIB-4) score (>= 1.3 for <= 65 years; >= 2.0 for >65 years). Logistic regression was used to identify independent predictors of high FIB-4. Results: A total of 61.4% of participants were women, the mean age was 51.3 +/- 14.4 years, and the mean BMI was 31.4 +/- 6.0 kg/m(2). MASLD prevalence was 75.7% (n = 10,873), rising with the number of CMRFs (56.5% with one factor vs. 83.4% with all). The prevalence of high FIB-4 scores was 12.0% overall, being lower in MASLD patients than non-MASLD patients (11.2% vs. 14.4%, p < 0.001). FIB-4 scores decreased with increasing BMI (28.1% underweight vs. 8.7% class III obesity). Male sex, T2DM, and hypertension independently predicted high FIB-4 scores, while smoking, higher BMI, and MASLD were inversely associated. Conclusions: Three-quarters of Turkish adults with CMRF have MASLD. Standard FIB-4 thresholds may underestimate fibrosis risk in obese and smoking populations, underscoring the need for adjusted cut-offs or alternative tools. This study is the first to provide nationwide MASLD prevalence data in Turkiye.
Keywords: MASLD; obesity; hypertension; type 2 diabetes mellitus; liver fibrosis; FIB-4 score